1980
DOI: 10.1136/jech.34.2.134
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mortality and two indicators of morbidity.

Abstract: SUMMARY The Resource Allocation Working Party concluded that standardised mortality ratios are the best available indicators of geographical variations in morbidity. In this paper we give the results of a statistical analysis of the relationship between mortality and two indicators of morbidity, obtained from the 1971 census, for three age groups. The level of aggregation in the data is comparable with that at district or area level. Strong linear relationships are obtained, suggesting that it is reasonable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…1 Mortality data can only provide a proxy for health rather than measure it directly, and there has been considerable debate about the limitations of the measure. [2][3][4][5][6] It has also been suggested that the inadequacy of the SMR as an indicator of morbidity would become more marked for lower levels of aggregation because of the smaller number of deaths involved, 3 although to date this suggestion has not been explored. 1 The introduction of a question on limiting long term illness (LLTI) in the 1991 UK census provided for the first time information on perceived levels of morbidity at the small area level.…”
mentioning
confidence: 99%
“…1 Mortality data can only provide a proxy for health rather than measure it directly, and there has been considerable debate about the limitations of the measure. [2][3][4][5][6] It has also been suggested that the inadequacy of the SMR as an indicator of morbidity would become more marked for lower levels of aggregation because of the smaller number of deaths involved, 3 although to date this suggestion has not been explored. 1 The introduction of a question on limiting long term illness (LLTI) in the 1991 UK census provided for the first time information on perceived levels of morbidity at the small area level.…”
mentioning
confidence: 99%
“…Other critics argued that the correlation of SMRs with General Household Survey morbidity data was even worse sub-regionally (Ferrer, Moore and Stevens 1977;Snaith 1978). However, in a much larger study, Brennan and Clare (1980) found strong correlations below Area Health Authority level between mortality and two measures of sickness from the national census. They concluded that overall mortality could justifiably be used sub-regionally as a proxy for morbidity in allocation.…”
Section: Mortality and Morbidity Correlationsmentioning
confidence: 93%
“…Wards were defined as level 1, travel to work areas as level 2 and standard regions as level 3 (subscripts i,jand k respectively). The response variable (Yijk) was the natural logarithm of the health outcome measure (SMRs, SIRs and SPSRs for males and females).…”
Section: Methodsmentioning
confidence: 99%